Deep-subwavelength focusing with self-similar chain of spoof plasmonic resonators at terahertz frequency - Dong, Zihao (2019)
The terahertz wave is an electromagnetic wave that has not been fully developed between microwave and infrared. Due to its penetrating robbing, frequency， and high spatial resolution, it is widely used in various fields. The acquisition of high-energy terahertz radiation sources is the premise of terahertz development. It has been recently shown that extremely thin textured copper disks can induce the multipolar spoof localized surface plasmons. The article is based on the self-similar chain of extremely thin textured copper disks as plasmonic resonators, the enhancement of terahertz radiation is realized from the simulation software. This system is a self-similar chain of several plasmonic resonators that gradually reduce size and separation. The results of the project can find potential applications in the terahertz field.